High resolution imaging of the magnetic field in the central parsec of the Galaxy - Roche, P; Lopez Rodriguez, E; Telesco, C; Schodel, R; Packham, C (Elsevier, 2018)
We discuss a high resolution (FWHM∼ 0:45 arcsec) image of the emissive polarization from warm dust in the minispiral in the Galactic Centre and discuss the implications for the magnetic field in the dusty filaments. The image was obtained at a wavelength of 12.5 μm with the CanariCam multimode mid-infrared imager on the Gran Telescopio Canarias. It confirms the results obtained from previous observations but also reveals new details of the polarization structures. In particular, we identify regions of coherent magnetic field emission at position angles of ∼ 45o to the predominantly north–south run of field lines in the Northern Arm which may be related to orbital motions inclined to the general flow of the Northern Arm. The luminous stars that have been identified as bow-shock sources in the Northern Arm do not disrupt or dilute the field but are linked by a coherent field structure, implying that the winds from these objects may push and compress the field but do not overwhelm it. The magnetic field in the low surface brightness regions in the East-West Bar to the south of SgrA* lies along the Bar, but the brighter regions generally have different polarization position angles, suggesting that they are distinct structures. In the region of the Northern Arm sampled here, there is only a weak correlation between the intensity of the emission and the degree of polarization. This is consistent with saturated grain alignment where the degree of polarization depends on geometric effects, including the angle of inclination of the field to the line of sight and superposition of filaments with different field directions, rather than the alignment efficiency.